Ternary eutectic electrolyte and preparation method and application thereof
Through the ternary eutectic electrolyte system composed of zinc perchlorate, acetamide and water molecules, the problem of narrow voltage window of the secondary zinc battery electrolyte and hydrogen evolution reaction is solved, and the electrode utilization rate and Coulomb efficiency of the battery are improved, thus achieving the realization of the realization of the battery. High discharge capacity and rate performance.
Patent Information
- Application Number
- CN202411111760.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-13
AI Technical Summary
The electrolytes of existing secondary zinc batteries have problems such as narrow voltage window, hydrogen evolution reaction, dendrite generation and electrode surface by-product generation, resulting in low electrode utilization and Coulomb efficiency, and low ionic conductivity of zinc salt eutectic electrolytes. , limiting its scale application.
Using a ternary eutectic electrolyte system composed of zinc perchlorate, acetamide and water molecules, the Lewis acid-base force and Zn2+ cluster configuration between components can improve ionic conductivity and reaction kinetics and build safety , stable and efficient electrolyte.
It significantly improves the polarization voltage, Coulomb efficiency and rate performance of the battery, enhances the kinetics of the electrochemical reaction, and achieves high discharge capacity and excellent rate performance.
Smart Images

Figure CN119133636A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary zinc ion batteries, and in particular to a ternary eutectic electrolyte and a preparation method and application thereof. Background Art
[0002] Secondary aqueous zinc batteries use zinc metal anodes and aqueous electrolytes, which are abundant and widely distributed. On the one hand, zinc metal has a high capacity (820Ah kg -1 and 5854Ah L -1 ), strong chemical stability, and high compatibility with aqueous solutions; on the other hand, aqueous electrolytes have the special advantages of low cost, high ion conductivity (about 100 times that of organic electrolytes), high safety, and environmental friendliness. In summary, the development of new secondary aqueous zinc batteries has important scientific significance and application value for the next generation of large-scale energy storage and conversion equipment.
[0003] As a medium for electrochemical reactions, the electrolyte plays an important role in battery operation. Its own physical and chemical properties have an important influence on the mass transfer ion solvation configuration, battery voltage window, positive electrode material stability, zinc anode deposition / precipitation reversibility, zinc metal deposition morphology, etc. The construction of high-performance secondary aqueous zinc batteries depends to a large extent on the rational design of efficient electrolytes. However, secondary zinc batteries based on ordinary low-concentration weakly acidic electrolytes still face challenges: 1) Narrow voltage window (<2V vs. Zn 2+ / Zn). The theoretical decomposition voltage of water solvent is 1.23V. As an important component of the electrolyte, it determines the narrow stable voltage window of the aqueous electrolyte. 2) Water decomposes hydrogen. Zn 2+ The theoretical potential of electron deposition (-0.76V vs. SHE) is significantly lower than the hydrogen evolution potential (0V vs. SHE), so the zinc deposition process is often accompanied by hydrogen evolution reaction. 3) Zinc negative electrode dendrites. The uneven ion concentration on the zinc electrode surface, the uneven electric field distribution and the Zn 2+ The special solvation structure causes zinc to tend to aggregate and nucleate at low energy during deposition, resulting in uneven deposition, inactive dead crystals and dendrites, and ultimately greatly reducing electrode utilization and coulombic efficiency. 4) Byproducts are generated on the electrode surface. Hydrogen evolution reaction, zinc electrode corrosion reaction and complex battery reaction mechanism will consume H + , causing the pH of the electrolyte to increase, and then the formation of by-products such as zinc oxide, zinc hydroxide and basic zinc salt precipitation.
[0004] To solve the above problems, the electrolyte regulation strategies reported so far mainly focus on reducing the water solvent content, inhibiting the activity of water molecules, and regulating the Zn 2+The solvation configuration is used to inhibit corrosion, hydrogen evolution, dendrites, pH instability and many other side reactions, so as to expand the battery's stable voltage window and improve the battery's energy density and cycle stability. Among them, the eutectic mixture formed by zinc salts and other compound ligands has many advantages such as non-volatile, high (electro)chemical stability, environmental friendliness, and strong designability. It has attracted much attention as a secondary zinc-iodine battery electrolyte. However, the ionic conductivity is low (<10mScm -1 , room temperature) and poor electrochemical reaction kinetics still restrict the large-scale application of zinc salt eutectic electrolytes. The reasons are as follows: (1) Zn in the eutectic system 2+ -The intermolecular forces between anions and ligands are strong, resulting in a low number of free ions, Zn 2+ The cluster configuration is large High viscosity (10-1000 times that of ordinary water / organic systems); (2) The eutectic system has irregular and randomly distributed "caves" And Zn 2+ Cluster migration follows the "cave theory" and only when Zn 2+ The cluster can only complete its migration when it enters a "cave" that is larger than its own volume through jumping migration. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention discloses a ternary eutectic electrolyte system that is easy to prepare, highly safe, environmentally friendly, and has high ionic conductivity. The eutectic system can improve ionic conductivity, enhance reaction kinetics, and is safe, stable, and efficient. The secondary zinc-iodine battery assembled with the eutectic system as the electrolyte has high discharge capacity, high coulombic efficiency, and excellent rate performance.
[0006] Specific technical solutions include:
[0007] A ternary eutectic electrolyte, the raw materials of which include zinc perchlorate, acetamide and water molecules.
[0008] In the ternary eutectic electrolyte system disclosed in the present invention:
[0009] The molar ratio of zinc perchlorate to acetamide is not higher than 1:3; the preferred molar ratio is 1:(3-18).
[0010] Based on the total volume of the eutectic mixture composed of zinc perchlorate and acetamide, the volume proportion of water molecules is 5-20%, which can be specifically selected from 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 18%, 20% or any value in the range. Preferably, it is 10-20%; more preferably, it is 10%.
[0011] The invention adopts zinc salt containing weak Lewis base anion and small molecule ligand compound-acetamide, and then reasonably introduces water as additive to regulate Lewis acid-base interaction between components and Zn 2+ Cluster configuration improves ionic conductivity, enhances reaction kinetics, and constructs a safe, stable, and efficient new zinc salt eutectic electrolyte system.
[0012] Experiments have found that if small molecule water is not added as an additive, or if other additives such as acetonitrile and dimethyl sulfoxide, which are common in the art, are added, the prepared eutectic electrolyte has high impedance and low conductivity; the battery assembled with the above eutectic electrolyte not only has an increased polarization voltage and a significantly decreased coulombic efficiency, but also a significantly decreased discharge capacity and rate performance.
[0013] It was also found through experiments that when zinc perchlorate is replaced by common organic zinc salts in the art, such as zinc trifluoromethanesulfonate, or inorganic zinc salts, such as zinc sulfate, it is impossible to form a eutectic reaction with the small molecule ligand compound-acetamide. This indicates that the ternary eutectic electrolyte system of zinc perchlorate-acetamide-small molecule water disclosed in the present invention has particularity.
[0014] The present invention also discloses a method for preparing the ternary eutectic electrolyte, comprising:
[0015] Zinc perchlorate and acetamide are mixed evenly to obtain a eutectic mixture, and water molecules are added as an additive, and the mixture is mixed evenly to obtain the ternary eutectic electrolyte.
[0016] Preferably, zinc perchlorate and acetamide are uniformly mixed under heating conditions, and the heating temperature is 40-100°C, and can be specifically selected from 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or any value within the range.
[0017] The invention also discloses a secondary zinc-iodine battery, which adopts the ternary eutectic electrolyte.
[0018] The positive electrode of the secondary zinc-iodine battery is selected from conventional types in the art, such as iodine element, conductive polymer / iodine composite material, Mxene / iodine composite material, etc.
[0019] The negative electrode of the secondary zinc-iodine battery is selected from conventional types in the art, such as a zinc metal negative electrode.
[0020] Preferably, the positive electrode is selected from activated carbon / iodine. Experiments have shown that this composite positive electrode material exhibits high reactivity.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention discloses a ternary eutectic electrolyte with simple preparation, high safety, environmental friendliness and high ion conductivity, which utilizes its formation principle and unique chemical environment, and simultaneously introduces a small amount of inorganic water molecule additives. On the one hand, it weakens the Lewis acid-base interaction between zinc salt-ligand compound molecules, improves ion conductivity and changes Zn 2+ On the other hand, water molecules participate in the construction of the eutectic system, and the activity and hydrogen bond strength are low. 2+ (De)solvation energy, migration path and interfacial mass transfer process, inducing orderly deposition of metallic zinc and improving the conversion reaction kinetics of iodine positive electrode materials.
[0023] The ternary eutectic electrolyte disclosed in the present invention is easy to synthesize, the components used are low-priced, and the ionic conductivity can reach up to 11.76 mS cm -1 Symmetrical cell at 1 mA cm -2 After continuous charge and discharge for 1 hour at a current density of , the polarization voltage is only about 40mV, which is significantly lower than that of the other three eutectic systems. When matched with the activated carbon / iodine composite positive electrode, the full battery cycle discharge capacity and rate performance are significantly higher. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The synthetic steps of Example 1, Comparative Example 6 and Comparative Example 8 are shown in FIG.
[0025] Figure 2 The impedance spectrum test data diagram of the eutectic electrolyte prepared in Example 1 and Comparative Examples 1 to 3 respectively;
[0026] Figure 3 The charge and discharge curves of the full battery assembled with the eutectic electrolyte system prepared in Example 1 and Comparative Examples 1 to 3 respectively;
[0027] Figure 4 The full-battery rate curves of the eutectic electrolyte systems prepared in Example 1 and Comparative Examples 1 to 3 are shown. DETAILED DESCRIPTION
[0028] In order to make the technical problems, technical solutions and advantages to be solved by the present invention easier to understand, the following will be described in detail in conjunction with the accompanying drawings and specific embodiments. However, it should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the art without making creative work are within the scope of protection of the present invention. Unless otherwise specified, the raw materials, reagents, and equipment involved in this article can be purchased or made by known methods.
[0029] Example 1
[0030] At room temperature, zinc perchlorate and acetamide were weighed in a molar ratio of 1:3, heated at 70° C. and uniformly mixed to obtain a eutectic mixture. Water molecules were added, the volume of which accounted for 10% of the volume of the eutectic mixture, and the electrolyte was obtained after standing for 12 hours.
[0031] Example 2
[0032] The preparation process is substantially the same as that in Example 1, except that the volume of the added water molecules is replaced to 5% of the volume of the eutectic mixture.
[0033] Example 3
[0034] The preparation process is substantially the same as that in Example 1, except that the volume of the added water molecules is replaced to account for 20% of the volume of the eutectic mixture.
[0035] Example 4
[0036] The preparation process is substantially the same as that in Example 1, except that the molar ratio of zinc perchlorate to acetamide is replaced with 1:18.
[0037] Comparative Example 1
[0038] The preparation process is substantially the same as that in Example 1, except that no water molecules are added.
[0039] Comparative Example 2
[0040] The preparation process is substantially the same as that in Example 1, except that the added water molecules are replaced with an equal volume of acetonitrile.
[0041] Comparative Example 3
[0042] The preparation process is substantially the same as that in Example 1, except that the added water molecules are replaced with an equal volume of dimethyl sulfoxide.
[0043] Comparative Example 4
[0044] The preparation process is substantially the same as that in Example 1, except that the molar ratio of zinc perchlorate to acetamide is replaced with 1:2.
[0045] It was observed that the eutectic reaction did not occur.
[0046] Comparative Example 5
[0047] The preparation process is substantially the same as that in Example 1, except that the added zinc perchlorate is replaced by an equimolar amount of zinc trifluoromethanesulfonate.
[0048] Comparative Example 6
[0049] The preparation process is substantially the same as that in Comparative Example 4, except that the molar ratio of zinc trifluoromethanesulfonate to acetamide is replaced with 1:12.
[0050] Comparative Example 7
[0051] The preparation process is substantially the same as that in Example 1, except that the added zinc perchlorate is replaced by an equimolar amount of zinc sulfate.
[0052] Comparative Example 8
[0053] The preparation process is substantially the same as that in Comparative Example 6, except that the molar ratio of zinc sulfate to acetamide is replaced with 1:12.
[0054] Figure 1 The synthetic step diagrams of Example 1, Comparative Example 6 and Comparative Example 8 show that even when the ratio of zinc trifluoromethanesulfonate to zinc sulfate to acetamide reaches 1:12, the eutectic reaction does not occur. However, when the molar ratio of zinc perchlorate to acetamide is less than or equal to 1:3, the eutectic reaction phenomenon occurs.
[0055] Performance Testing:
[0056] 1. Commercial zinc foil (thickness: 80 μm, diameter: 12 mm) was used as the positive and negative electrodes of the symmetrical battery, glass fiber was used as the separator, and the products prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were used as the electrolyte to assemble CR2025 button batteries. Constant current charge and discharge tests were performed on the blue battery test system. The working current density was 1 mA cm -2 The charge and discharge time is 0.5 h, and the surface capacity is 0.5 mAh cm -2 , the polarization voltage results of the symmetrical battery are shown in Table 1 below.
[0057] Table 1
[0058]
[0059] In Table 1, it can be seen from the comparison between Example 1 and Comparative Examples 1 to 3 that the polarization voltage of the symmetrical cell using the zinc perchlorate-acetamide binary eutectic electrolyte (Comparative Example 1) is the largest, followed by the polarization voltage of the symmetrical cell using the zinc perchlorate-acetamide-dimethyl sulfoxide ternary eutectic electrolyte (Comparative Example 3), followed by the zinc perchlorate-acetamide-acetonitrile ternary eutectic electrolyte (Comparative Example 2), and the smallest polarization voltage is the zinc perchlorate-acetamide-water ternary eutectic electrolyte (Example 1). This shows that the additive molecules can effectively improve the ionic conductivity of the eutectic system and reduce the polarization of the electrode interface, and the water molecule additive has the most obvious effect.
[0060] By comparing Examples 1 to 3, it can be seen that increasing the content of water molecule additives can significantly reduce the polarization voltage of the symmetrical battery. When the volume of the additive accounts for 10% and 20% of the volume of the eutectic mixed system, the symmetrical batteries all show lower polarization voltages, which are lower than the system with a volume ratio of 5%.
[0061] 2. Commercial copper foil (thickness: 20 μm, diameter: 12 mm) was used as the positive electrode of the asymmetric battery, commercial zinc foil was used as the negative electrode of the asymmetric battery, and glass fiber was used as the separator. The products prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were used as electrolytes to assemble CR2025 button-type asymmetric batteries. The zinc metal deposition / stripping coulomb efficiency test was performed on the blue battery test system. The working current density was 0.5 mA cm -2 , the discharge time is 1h, the charging voltage is 0.5V, and the coulombic efficiency results based on different electrolytes are shown in Table 2 below.
[0062] Table 2
[0063]
[0064] In Table 2, it can be seen from the comparison between Example 1 and Comparative Examples 1 to 3 that in the initial activation stage, the coulombic efficiency of the four eutectic electrolytes fluctuated greatly and were unstable. The main reason is that the eutectic system needs to establish matching with the zinc metal electrode, which limits the high-efficiency deposition and stripping of the zinc electrode. After activation, the asymmetric battery based on the zinc perchlorate-acetamide-water ternary eutectic electrolyte has the highest coulombic efficiency and tends to be stable, indicating that this eutectic system has a stronger matching with the zinc metal electrode. It can be seen from the comparison between Examples 1 to 3 that in the initial activation stage, the coulombic efficiency of the three eutectic electrolytes fluctuated greatly and were unstable. After activation, the asymmetric battery based on the zinc perchlorate-acetamide-water ternary eutectic electrolyte with a volume ratio of 10% has the highest coulombic efficiency and tends to be stable, indicating that this eutectic system has a stronger matching with the zinc metal electrode. Therefore, the higher the content of water molecule additives, the better.
[0065] 3. Under room temperature, commercial stainless steel foils were used as the positive and negative electrodes of the symmetrical battery, glass fiber was used as the separator, and the products prepared in Example 1 and Comparative Examples 1 to 3 were used as the electrolyte to assemble a CR2025 button-type asymmetric battery. The impedance test was performed using an electrochemical workstation system. The test conditions were: 100mHZ-100KHz, disturbance voltage: 5mV, and the impedance spectrum test data of different electrolytes were shown in the figure below. Figure 2 As shown. Then, the ionic conductivity of four different electrolytes is calculated according to formula 1.
[0066] σ=GL / A=L / RA Formula 1
[0067] σ(S cm -1 ): ionic conductivity, G(S): conductivity, R: electrolyte resistance, L(cm): distance between two electrodes, A(cm 2 ): electrode area.
[0068] Figure 2a, b are the impedance spectrum test data of four different eutectic electrolytes. From the electrolyte resistance values in the figure, it can be seen that the zinc perchlorate-acetamide binary eutectic electrolyte has the largest resistance, followed by zinc perchlorate-acetamide-dimethyl sulfoxide and zinc perchlorate-acetamide-acetonitrile ternary eutectic electrolytes, and the zinc perchlorate-acetamide-water ternary eutectic electrolyte has the smallest resistance value and the corresponding ionic conductivity is the largest. The calculation results show that the ionic conductivity of the electrolyte prepared in Example 1 is 11.76mS cm -1 The ionic conductivity of comparative example 1 is 2.01 mS cm -1 The ionic conductivity of comparative example 2 is 7.84 mS cm -1 The ionic conductivity of comparative example 3 is 3.53 mS cm -1 .
[0069] 4. Use activated carbon / iodine positive electrode material, mix it with conductive carbon black and binder polytetrafluoroethylene (PVDF) in a mass ratio of 7:2:1 in N-methylpyrrolidone solvent. Apply the above mixed viscous paste to the stainless steel mesh current collector and vacuum dry it to obtain the positive electrode sheet after drying. Use four different eutectic electrolytes of Example 1 and Comparative Examples 1 to 3 and commercial zinc foil to assemble CR2025 button-type full batteries. Use the blue battery test system, test conditions: voltage test range is 0.2~1.6V, current density is 1.25~10Ag -1 (calculated based on the mass of iodine), determine the battery discharge capacity and rate performance, charge and discharge curves and rate performance such as Figure 3 and 4 The specific values are listed in Tables 3 and 4 below.
[0070] Figure 3 The figure is a charge and discharge curve diagram of a full battery assembled using four different eutectic electrolyte systems. It can be seen that the activated carbon / iodine positive electrode material shows the same charge and discharge curve shape in the above four different eutectic electrolytes, indicating that the charge and discharge process is the same, and the discharge capacity of the zinc-iodine battery based on the zinc perchlorate-acetamide-water ternary eutectic electrolyte (Example 1) is significantly higher than that of the other three electrolyte systems, and the charge and discharge specific capacity values are shown in Table 3, indicating that the ternary eutectic electrolyte disclosed in the present invention is conducive to the full progress of the electrochemical reaction.
[0071] Figure 4 The figure is a full-cell rate curve diagram assembled with four different eutectic electrolytes. It can be seen that the discharge capacity of the zinc-iodine battery based on zinc perchlorate-acetamide-water ternary eutectic electrolyte at different current densities is significantly higher than that of the other three electrolyte systems. The discharge specific capacity values at different current densities are shown in Table 4. The results are consistent with Figure 3The results are similar, indicating that the ternary eutectic electrolyte disclosed in the present invention is conducive to the full electrochemical reaction of the activated carbon / iodine positive electrode, and the water molecule additive is crucial.
[0072] Table 3
[0073]
[0074] Table 4
[0075]
[0076] The above-mentioned embodiments are preferred embodiments, but the protection scope of the present invention is not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above-mentioned embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.
Claims
1. A ternary eutectic electrolyte, characterized in that: The raw material composition includes zinc perchlorate, acetamide and water molecules; The molar ratio of zinc perchlorate to acetamide is not higher than 1:3; Based on the total volume of the eutectic mixture composed of zinc perchlorate and acetamide, the volume of water molecules accounts for 5 to 20%.
2. The ternary eutectic electrolyte according to claim 1, characterized in that: The molar ratio of zinc perchlorate to acetamide is 1:(3-18).
3. The ternary eutectic electrolyte according to claim 1, characterized in that: Based on the total volume of the eutectic mixture composed of zinc perchlorate and acetamide, the volume of water molecules accounts for 10-20%.
4. The ternary eutectic electrolyte according to claim 1, characterized in that: Based on the total volume of the eutectic mixture composed of zinc perchlorate and acetamide, the volume of water molecules accounts for 10%.
5. A method for preparing a ternary eutectic electrolyte according to any one of claims 1 to 4, characterized in that: include: Zinc perchlorate and acetamide are mixed evenly to obtain a eutectic mixture, and water molecules are added as an additive, and the mixture is mixed evenly to obtain the ternary eutectic electrolyte.
6. The method for preparing a ternary eutectic electrolyte according to claim 5, characterized in that: The zinc perchlorate and acetamide are mixed uniformly under heating conditions, and the heating temperature is 40-100°C.
7. A secondary zinc-iodine battery, characterized in that: The ternary eutectic electrolyte according to any one of claims 1 to 4 is used.
8. The secondary zinc-iodine battery according to claim 7, characterized in that: The positive electrode is selected from an activated carbon / iodine composite material.
